The socio-cognitive architecture of the discourse of meaning making as part of the CLIL learning experience: a case study at primary level with limited English students in a Romanian context - Hawker, Irina Adriana (2013)
This study focuses on limited English students’ cognitive engagement generated through learning interactions with others and tasks under a content-driven and discovery-oriented CLIL learning arrangement in a primary school setting. The main aims are: to explore students’ capability to access and inhabit learning spaces within the L2 mediated discourse; to investigate the potential the CLIL learning experience has to sustain dialogic learning and thinking of a higher order; and finally, to make a contribution to the debate over the potential of the CLIL learning experience to promote deep learning and foster life-long learning competencies. At the heart of its theoretical underpinning lies the idea that cognition develops through the merging of the social with the individual which points towards the need to corroborate a socio-cognitive theoretical framework. Thus, the investigation is conceptualised within the ‘inter-mental development zone’ (Mercer and Littleton, 2007), under the auspices of dialogic learning (Wells, 2001b), and in cognisance of the individual’s active construction of knowledge (Bruner, 1985; van Dijk’s, 2006a). This theoretical line originates in the, now, classic theoretical constructs of Zone of Proximal Development and the More Knowledgeable Other from Vygotsky (1978), and the notion of scaffolding from Wood, Bruner and Ross (1976). With regard to the methodological design, this explorative study falls under the qualitative paradigm within the boundaries of a case study, and corroborates close observations of the learning behaviours with introspective methods. A multilayered analysis is employed which allows elements from various contextual layers and dimensions to enrich the analytical insight. In addition, a fine grained-analysis is pursued regarding the dynamics as well as the substance of the learning events, which conveys a systematic and holistic investigation of the learning phenomenon. The findings of this study suggest that the CLIL approach be regarded as a learning interaction of three foci whereby alongside content-grounded and language-oriented strands run equally well-represented management-of-the-learning strands. Further, it is proposed that a reasonable level of ambiguity stemming from presenting content in the medium of a foreign language and from exposing students to new intriguing facts, prompts cognitive conflict thus giving rise to explorative conversational digressions which bring added cognitive value to the peer-sustained learning interaction. Moreover, this investigation also highlights the complementarity between conversational and instructional units on three levels of cognitive engagement (propositional, linguistic and managerial). Finally, an ability to activate and manipulate different manifestations of knowledge is documented. If this ability would be nurtured long-term, then a disposition for inquiry and criticality as well as an enhanced metacognitive awareness can develop which may translate into skills transferable across the curriculum. Overall, the study recommends the CLIL approach as a rich cognitive medium for learning, and an asset for promoting quality learning with the specification that its implementation needs careful context-bound consideration.